2004
DOI: 10.1159/000081033
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Levofloxacin and Ciprofloxacin in Combination with Cefepime, Ceftazidime, Imipenem, Piperacillin-Tazobactam and Amikacin against Different <i>Pseudomonas aeruginosa</i> Phenotypes and <i>Acinetobacter</i> spp.

Abstract: Background: Combination therapy is used to widen the antimicrobial spectrum, minimize toxicity and prevent the emergence of resistant mutants. Methods: Synergy between levofloxacin or ciprofloxacin and ceftazidime, cefepime, imipenem, piperacillin-tazobactam and amikacin was evaluated by checkerboard assay with 55 strains and by time-kill curves with 8 strains of Pseudomonasaeruginosa and Acinetobacter spp. Results: In the checkerboard assay, synergy and additivity were the most frequent effects observed among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 27 publications
2
17
1
Order By: Relevance
“…Treatment of P. aeruginosa clinical isolates with ciprofloxacin in combination with amikacin or gentamicin showed either synergistic, additive, or indifferent effects (31)(32)(33). Our results with the PAO1 strain are consistent with these previous observations since we observed no antagonistic effect of the ciprofloxacin-amikacin combination.…”
supporting
confidence: 92%
“…Treatment of P. aeruginosa clinical isolates with ciprofloxacin in combination with amikacin or gentamicin showed either synergistic, additive, or indifferent effects (31)(32)(33). Our results with the PAO1 strain are consistent with these previous observations since we observed no antagonistic effect of the ciprofloxacin-amikacin combination.…”
supporting
confidence: 92%
“…There are many reports in the literature on synergism with several rates observed with quinolone and beta-lactam antibiotics 26-30. In our study, synergy was not demonstrated in resistant strains with imipenem-ciprofloxacin combination while synergy was observed in 8% of the susceptible strains.…”
Section: Discussioncontrasting
confidence: 58%
“…The studies involving combination therapy with either sulbactam or the polymyxins that are described above form the major and most promising group. Other combinations have also been studied using in vitro techniques and animal models, including various combinations of quinolones, ␤-lactams, and/or amikacin (45,80,139,280,467). The results for quinolone combination therapy are varied, with reduced efficacy being described when ciprofloxacin was used for ciprofloxacin-resistant A. baumannii (151), as well as a lack of enhanced activity with levofloxacin combined with imipenem or amikacin in a mouse pneumonia model (273).…”
Section: Other Combination Therapymentioning
confidence: 99%